A IMPORTÂNCIA DO “NÃO” NA CONSTITUIÇÃO DO SUJEITO - Amaral, Luiz Felipe Vieira; Goi, Joana Patias; Drügg, Ângela Maria Schneider; Siqueira, Aparecida De Fátima Hortencio; Rodrigues, João Vitor Alegranzi (Salão do Conhecimento, 2018)
Estágio Básico em Psicologia 1